1988
DOI: 10.1042/bj2540391
|View full text |Cite
|
Sign up to set email alerts
|

GTP analogues promote release of the α subunit of the guanine nucleotide binding protein, Gi2, from membranes of rat glioma C6 BU1 cells

Abstract: The major pertussis-toxin-sensitive guanine nucleotide-binding protein of rat glioma C6 BU1 cells corresponded immunologically to Gi2. Antibodies which recognize the alpha subunit of this protein indicated that it has an apparent molecular mass of 40 kDa and a pI of 5.7. Incubation of membranes of these cells with guanosine 5'-[beta gamma-imido]triphosphate, or other analogues of GTP, caused release of this polypeptide from the membrane in a time-dependent manner. Analogues of GDP or of ATP did not mimic this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…The data described in this report are generally consistent with this model. Some investigators have observed a slow, fractional release of ao and ai2 from cultured cell membranes exposed to poorly hydrolyzed analogs of GTP (29,30). We (unpublished results) and others (6,31) have not observed release of native a subunits from membranes by analogs of GTP or by hormones.…”
Section: Resultsmentioning
confidence: 86%
“…The data described in this report are generally consistent with this model. Some investigators have observed a slow, fractional release of ao and ai2 from cultured cell membranes exposed to poorly hydrolyzed analogs of GTP (29,30). We (unpublished results) and others (6,31) have not observed release of native a subunits from membranes by analogs of GTP or by hormones.…”
Section: Resultsmentioning
confidence: 86%
“…Surprisingly enough, the present results argue against the involvement of any of the traditional transmembrane signals in this binding process. However, it was recently demonstrated that pertussis toxin did not prevent the dissociation between the o~-and the/33,-subunits, even if the a-subunit was efficiently ribosylated (28). Consequently, any involvement of the dissociation process itself or the/33,-subunit in cellular regulation can not be adequately tested with pertussis toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial down-regulation of G,a from cell membranes has been observed in L6 skeletal myoblasts treated with cholera toxin to ADP ribosylate the G-proteins [7], although under these conditions the G , a lost from the plasma membrane was not detected intracellularly and is presumed to have been degraded. By contrast, non-hydrolysable guanine nucleotide analogues can displace both G , a [7] and G , a [8] from purified plasma membranes in vitro. However, in concurrence with our observations, translocation of a G-protein from the plasma membrane of intact cells during hormonal stimulation remains to be demonstrated.…”
Section: Biochemical Society Transactionsmentioning
confidence: 94%